Antimicrobial Peptide Expression at the Ocular Surface and Their Therapeutic Use in the Treatment of Microbial Keratitis - Shannon, Allison H.; Adelman, Sara A.; Hisey, Erin A.; Potnis, Sanskruti S.; Rozo, Vanessa; Yung, Madeline W.; Li, Jennifer Y.; Murphy, Christopher J.; Thomasy, Sara M.; Leonard, Brian C. (Frontiers in Microbiology, 2022)
Microbial keratitis is a common cause of ocular pain and visual impairment worldwide. The ocular surface has a relatively paucicellular microbial community, mostly found in the conjunctiva, while the cornea would be considered relatively sterile. However, in patients with microbial keratitis, the cornea can be infected with multiple pathogens including Staphylococcus aureus, Pseudomonas aeruginosa, and Fusarium sp.. Treatment with topical antimicrobials serves as the standard of care for microbial keratitis, however, due to high rates of pathogen resistance to current antimicrobial medications, alternative therapeutic strategies must be developed. Multiple studies have characterized the expression and activity of antimicrobial peptides (AMPs), endogenous peptides with key antimicrobial and wound healing properties, on the ocular surface. Recent studies and clinical trials provide promise for the use of AMPs as therapeutic agents. This article reviews the repertoire of AMPs expressed at the ocular surface, how expression of these AMPs can be modulated, and the potential for harnessing the AMPs as potential therapeutics for patients with microbial keratitis.